PEMECAHAN MASALAH SISWA KELAS V SDN 1 SUWATU PADA MATERI MENGUKUR DAN MEMBANDINGKAN SUDUT MELALUI PENDEKATAN MATEMATIKA REALISTIK - Fabria Khabib Ulil Asror; Ervina Eka Subekti; Filia Prima Atharina3 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of Realistic Mathematics Approach (RMA) on the problem-solving ability of fifth grade students of SDN 1 Suwatu on the material of measuring and comparing angles. The One-Group Pretest-Posttest Design research design with the Pre-experimental method was used. The pretest results showed that the average student score was 58.65 (not yet completed the KKM 75), while the posttest showed a significant increase with an average of 85.57 (completed the KKM). The Paired Sample t-test showed a significance value of 0.000 (<0.05), indicating a significant difference between the pretest and posttest scores. The average N-Gain score of 0.659 (moderate category) and a percentage of 65.90% (quite effective) strengthen that RMA positively influences students' problem-solving abilities. The use of wall clock media and the association of concepts with everyday life have been shown to increase students' enthusiasm and understanding.